Sculpture in print, 1480-1600 - Bloemacher, Anne, 1980-; Richter, Mandy; Faietti, Marzia (Brill's studies on art, art history, and intellectual history, 2021)
"Sculpture in Print, 1480-1600 is the first monograph dedicated to the intriguing history of the translation of statues and reliefs into print. The multitude of engravings, woodcuts and etchings show a highly creative handling of the 'original' antique or contemporary work of art. The essays in this volume reflect these various approaches to and challenges of translating sculpture in print. They analyze foremost the beginnings of the phenomenon in Italian and Northern Renaissance prints and they highlight by means of case studies amongst many other topics the interrelated terminology between sculpture and print, lost models in print, the inventive handling of fragments, as well as the transformation of statues into narrative contexts"--